Coinfections and differential diagnosis in immunocompetent patients with uveitis of infectious origin (2019)
Background: Making a definite diagnosis of infectious uveitis is a challenging task because many other infectious, and non-infectious uveitis, may have similar non-specific symptoms and overlapping clinical appearances. Co-infections in immunocompetent patients are not frequently proved with traditional serologic-diagnostic tools. Methods: Descriptive transversal study, in a Uveitis Service of an Ophthalmology Reference Center, in Bogotá, Colombia, from July 2014 to February 2016. Aqueous humor (AH) and/or vitreous fluid, blood and serum samples were collected from consecutive patients suspected of having infectious uveitis. The diagnosis of ocular toxoplasmosis (OT) was confirmed by the Goldmann-Witmer coefficient (GWC) and by polymerase chain reaction (PCR). Differential diagnosis by PCR in AH was done for viral origin such as Cytomegalovirus (CMV), Herpes simplex virus type 1 (HSV1), Herpes simplex virus type 2 (HSV2), Varicella zoster virus (VZV), Epstein-Barr virus (EBV) and Mycobacterium tuberculosis. Results: In 66 Colombian patients with uveitis of presumed infectious origin: 22 (33.3%) were confirmed as OT, 16 (24.2%) as undetermined OT, five (7.5%) as co-infections and 23 (34.8%) as other uveitis. Toxoplasma coinfection with M. tuberculosis was identified in one case by PCR and in four cases with HSV by GWC. The initial clinical diagnosis changed, after laboratory examination, in 21 cases (31.8%). Conclusions: Clinical diagnosis can be changed by laboratory examination in a significant proportion of cases of uveitis. Diagnosis of OT should combine the use of PCR and GWC to reach the maximum of confirmation of cases. The use of multiple laboratory methods is necessary to identify co-infections and viral infections that can mimic OT in immunocompetent patients. © 2019 The Author(s).